Edge search position - Valiente, Silvia Carina (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2020)
This article recovers some of the productions of the Colombian historian and popular educator Alfonso Torres Carrillo made in the last ten, precursor of the so-called edge research proposal, theoretical-methodological and ethical-political option. With the aim of positioning this proposal, while linking its contribution with contemporary thinkers in the region, I hope from this work to contribute to the dissemination of qualitative, dialogical and participatory critical methodologies characterized by centrality in the subject and subjectivity, the displacement of objectivity towards reflexivity and solidarity in collective processes of knowledge construction.